Intraoperative mapping of the right hemisphere: a systematic review of protocols that evaluate cognitive and social cognitive functions - Martín-Monzón, Isabel; Amores-Carrera, Laura; Sabsevitz, David; Herbet, Guillaume (Frontiers in Psychology, 2024)
The right hemisphere is often referred to as the nondominant hemisphere, which is meant to highlight the specialized role of the left hemisphere in language, but the use of this term runs the risk of oversimplifying or minimizing the essential functions of the right hemisphere. There is accumulating evidence from functional MRI, clinical lesion studies and intraoperative mapping data implicating the right hemisphere in a diverse array of cognitive functions, including visuospatial functions, attentional processes, and social cognitive functions. Neuropsychological deficits following right hemisphere resections are well documented but there is general paucity of literature focusing on how to best map these functions during awake brain surgery to minimize such deficits. To address this gap in the literature, a systematic review was conducted to examine the cognitive and emotional processes associated with the right hemisphere and the neuropsychological tasks frequently used for mapping the right hemisphere during awake brain tumor surgery. Considering the frequency of articles selected for each cognitive and social cognitive function, it was found that the most employed tests to assess language and speech functions in patients with lesions in the right cerebral hemisphere were a naming task and Pyramids and Palm Trees Test (PPTT). Spatial cognition was typically evaluated using the line bisection task, while social cognition was assessed through Reading the Mind in the Eyes (RME) test. The dual task and the movements of upper and lower limbs were the most frequently used methods to evaluate motor/sensory functions, and executive functions were typically assessed using the N-back test and Stroop test.To the best of our knowledge, this is the first comprehensive review to help provide guidance on the cognitive functions most at risk and methods to map such functions during right awake brain surgery.